Implementasi Penerapan Budaya Kaizen dalam Meningkatkan Mutu Pendidikan di Sekolah - Rani Irmayanti (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2024)
When we want change in our lives, we often expect immediate and drastic changes. We hope that this change will soon have a significant impact on our lives. But usually, we focus too much on results, don't commit to long-term changes, and the results are not optimal. Apart from building motivation and strong intentions, you must also develop habits and continuous improvement. Things like this are known based on the Japanese cultural principle of "Kaizen". Even the smallest changes in education can significantly impact improving the quality of education in schools. To maintain the quality of education in schools, there needs to be a significant increase in the level of education, through utilizing all instructional strategies and procedures used by teachers, educators, and students. The 5S concept (Seiri, Seiso, Seiton, Seiketsu, and Shitsuke), the PDCA concept, the 5W1H concept, and the 3M concept (Muda, Mura, and Muri) are some of the concepts that the Kaizen concept can justify to improve the quality of education. The process of collecting data through library research involves reading books, papers, journals, and other references to understand and analyze the theories presented in many literary works relevant to the topic. According to research findings, implementing kaizen culture in schools can have a positive effect on the field of education. In terms of efficiency or HR involvement as well as costs and time in implementation, this makes it possible to prevent waste and minimize failures in these activities because the implementation of educational activities through kaizen culture will be fully controlled and protected from sudden educational changes. Both in terms of curriculum, class management, extracurriculars, skills development, routine school activities, and providing learning.